SPECIES DIVERSITY OF FORESTS AS A MAIN RESOURCE FOR ASSESSING THEIR ECOSYSTEM FUNCTIONS IN THE NORTHERN STEPPE OF UKRAINE - Matushevych, Liubov; Lakyda, Petro (Forestry Education and Science: Current Challenges and Development Prospects, 2026)
Assessing the ecosystem functions of forests in regions with increased anthropogenic load on the environment in the context of global climate change is an urgent task. The forests of the Northern Steppe of Ukraine perform mainly ecological and social functions and their role in the stabilizing function of the environment is extremely important. To model the main ecosystem functions of the region's forests (carbon storage, oxygen productivity), an aggregation of the valuation parameters of forest stands from the separate database of the State Forestry Agency of Ukraine as of 2024 was carried out. At the same time, the main attention was paid to the parametric structure of the main forest-forming species of the region, which together form 80.1% of the area and 87.7% of the forest reserve of the northern steppe of Ukraine (common oak, Scots pine, robinia pseudoacacia and common ash).